Meningkatkan Kualitas Informasi dalam Bersosial Media Melalui Media Internet di Kampus IBI KOSGORO, Kota Jakarta - Rifiyanti, Hafizah (Jurnal Pengabdian Teratai, 2020)
The Internet facilitates everyone to interact in cyberspace, connecting people who are in distance. Through the internet, people can also access various social media platforms. Social media is at the core of a very primary need around the world with a huge number of users. Social media is a form of media transformation in today's sophisticated era. Social media gives people the freedom to express, to share opinions, do business, shop and to learn something as well. Besides, Social media can also have a negative impact if users don't use social media wisely and intelligently. Spending too much in social media can lead to poor sleep and numerous studies have shown that many negative impacts occurred in social media. Among young people, social media is used more for fun like posting photos, talking to friends, or doing something as simple as just checking what someone else is doing. The quality of utilizing social media as a useful medium for learning is still not done effectively, especially among students. This is also a concern that occurs among studens of IBI Kosgoro 1957, to improve the quality of social media information by using the internet media. Therefore, a training was conducted to pay special attention to improving the quality of social media information in the IBI Kosgoro 1957 campus. Keywords: social media, internet, communication media, networking